2018
DOI: 10.14283/jpad.2018.29
|View full text |Cite
|
Sign up to set email alerts
|

Pimavanserin: Potential Treatment for Dementia-Related Psychosis

Abstract: Psychosis is common across dementia types with a prevalence of 20% to 70%. Currently, no pharmacologic treatment is approved for dementia-related psychosis. Atypical antipsychotics are frequently used to treat these disorders, despite significant safety concerns. Pimavanserin, a selective 5-HT2A inverse agonist/antagonist, was approved in the U.S. for treating hallucinations and delusions associated with Parkinson’s disease psychosis (PDP). Patients in the pimavanserin group experienced a significant (p=0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 54 publications
0
42
1
Order By: Relevance
“…Depending on dementia type and increasing with disease progression, approximately 20%-70% of patients will experience dementia-related psychosis (DRP), characterized by delusions and hallucinations. 9 This estimate is thought to increase to more than 90% if behavioral symptoms such as dementia-related agitation and aggression are included as indicators of psychosis. 10 In a study by Peters et al (2015), DRP was associated with a more rapid progression to severe dementia (hazard ratio = 2.007; P = 0.028) and earlier death (hazard ratio = 1.537; P = 0.011) among patients with Alzheimer disease.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Depending on dementia type and increasing with disease progression, approximately 20%-70% of patients will experience dementia-related psychosis (DRP), characterized by delusions and hallucinations. 9 This estimate is thought to increase to more than 90% if behavioral symptoms such as dementia-related agitation and aggression are included as indicators of psychosis. 10 In a study by Peters et al (2015), DRP was associated with a more rapid progression to severe dementia (hazard ratio = 2.007; P = 0.028) and earlier death (hazard ratio = 1.537; P = 0.011) among patients with Alzheimer disease.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Pimavanserin effectively reduced hallucinations and delusions associated with DRP in multiple clinical studies, which included patients with the major forms of dementia, and was well tolerated by elderly fragile patients in the studies [33][34][35][36][37]149]. The purpose of this review was to identify mechanisms that explain the role of 5-HT 2A Rs in both the etiology and treatment of DRP.…”
Section: Discussionmentioning
confidence: 99%
“…Hallucinations, in particular, are associated with a 1.6-and 1.5-times higher risk of institutionalization and death, respectively (Scarmeas et al, 2005), and with reduced quality of life, subjective wellbeing and life satisfaction (Choi et al, 2021). Furthermore, dementia-related psychosis is associated with a significant increase in care partner burden (Aarsland, Larsen, Karlsen, Lim, & Tandberg, 1999;Cummings et al, 2018;Jeste & Finkel, 2000), and much of the responsibility of caring for individuals with dementia-related psychosis falls on family members. One study found that over 80% of care hours for individuals with probable dementia are provided informally by family care partners (Friedman, Shih, Langa, & Hurd, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There are no therapies currently approved by the U.S. Food and Drug Administration (FDA) for treating dementia-related psychosis (Cummings et al, 2018). Persons with dementia are often treated on a short-term basis with existing antipsychotic medications; however, these are associated with known risks and uncertain benefit (Kales, Gitlin, & Lyketsos, 2015;L.…”
Section: Introductionmentioning
confidence: 99%